Peer review of grant applications: a simple method to identify proposals with discordant reviews. - Bruno Giraudeau; Clémence Leyrat; Amélie Le Gouge; Julie Léger; Agnès Caille (PLoS ONE, 2011)
Grant proposals submitted for funding are usually selected by a peer-review rating process. Some proposals may result in discordant peer-review ratings and therefore require discussion by the selection committee members. The issue is which peer-review ratings are considered as discordant. We propose a simple method to identify such proposals. Our approach is based on the intraclass correlation coefficient, which is usually used in assessing agreement in studies with continuous ratings.